Intelligent RPA for Urban Permit Application Workflows - Anh, Nguyễn Minh; Bảo, Trần Quốc; Phúc, Lê Hoàng (International Journal of Technology and Modeling, 2024)
The digital transformation of urban management has paved the way for the integration of intelligent systems aimed at optimizing municipal workflows. One such system is Robotic Process Automation (RPA), which, when enhanced with Artificial Intelligence (AI), offers substantial improvements in automating repetitive tasks. This paper explores the application of Intelligent RPA in urban permit application workflows, specifically focusing on its potential to streamline the processes of permit requests, review, approval, and issuance in urban governance. The paper begins by identifying the current inefficiencies within traditional urban permit systems, such as delays in processing times, human errors, and lack of transparency. By integrating AI-driven decision-making capabilities, Intelligent RPA offers solutions to mitigate these issues, enabling real-time processing, predictive analytics for decision support, and seamless interaction across multiple government departments. Furthermore, this system can adapt to dynamic urban environments, accommodating changes in regulations or requirements. We present a conceptual framework that combines machine learning algorithms and natural language processing (NLP) to automate document verification, permit categorization, and policy compliance checks. The proposed system not only reduces operational costs and processing times but also improves citizen satisfaction by providing faster, more transparent services. The paper concludes with an analysis of potential challenges, including system integration complexities and data privacy concerns, while highlighting future directions for research in intelligent RPA within the context of smart cities.